SAT0186 Effects of denosumab, a subcutaneous rankl inhibitor, on the progression of structural damage in japanese patients with rheumatoid arthritis treated with csdmards: results from the 12-month double blind phase 3, desirable study. (15th June 2017) - Takeuchi, T; Tanaka, Y; Soen, S; Yamanaka, H; Yoneda, T; Tanaka, S; Nitta, T; Okubo, N; Genant, HK; Heijde, D van der
Abstract : Background: Denosumab is a fully human monoclonal antibody (IgG2 subclass) that inhibits bone resorption by inhibiting RANKL, a key mediator of osteoclast formation, function, and survival. Objectives: To evaluate the effect of denosumab 60 mg every 6 months (Q6M) or every 3 months (Q3M) on the progression of joint damage in Japanese patients with RA on csDMARD background treatment. Methods: DESIRABLE is a 12-month randomized, double-blind, placebo-controlled, parallel-group study in patients with RA receiving csDMARD treatment. Subjects fulfilling the 1987 ACR criteria or 2010 ACR-EULAR criteria were randomized (1:1:1) to denosumab 60 mg Q6M, denosumab 60 mg Q3M, or placebo. The primary endpoint is the change from baseline to 12 months in the van der Heijde modified total Sharp score (mTSS). Radiographs of hands and feet at baseline, 6 months and 12 months were scored with blinded time order by 2 readers independently. Average score of the 2 readers is used for the analysis. Comparisons of each denosumab group with placebo for the change from baseline were performed using van Elteren stratified rank test adjusting for baseline glucocorticoid use. Missing scores were imputed using linear extrapolation/interpolation. Results: Among 679 patients randomized, 667 (placebo, n=223; Q6M, n=222; Q3M, n=222) received at least one dose of study drug, and 60 (placebo n=15; Q6M, n=23; Q3M, n=22) were discontinued during the study. Demographic and baseline characteristics were similar across the groups (Table 1). Mean change from baseline in mTSS and erosion score (ES) at 12 months was significantly lower with both denosumab 60 mg Q6M and Q3M compared with placebo, with no obvious evidence of an effect on joint space narrowing (JSN) score for denosumab. (Table 2). Consistently, the percent of nonprogressors (ie, mTSS change ≤0.5) at 12 months was significantly greater with denosumab 60 mg Q6M (75.6%, p=0.010) and Q3M (78.1%, p=0.001) compared with placebo (64.2%). Incidence of adverse events (AEs), serious AEs, and AEs leading to discontinuation of study drug were similar across treatment groups. No events of osteonecrosis of the jaw or atypical femoral fracture were observed. Conclusions: Denosumab inhibited the progression of joint destruction significantly more than placebo and was generally well tolerated in Japanese patients with RA on csDMARDs. Denosumab has potential to be a new therapeutic option to inhibit structural progression for patients with RA. Disclosure of Interest: T. Takeuchi Grant/research support from: Astellas, Bristol-Myers Squibb, Chugai, Daiichi Sankyo, Eisai, AYUMI Pharmaceutical, Takeda, Teijin Pharma, AbbVie, Asahi Kasei Pharma, and Taisho Toyama, Consultant for: AstraZeneca, Eli Lilly, Novartis, Mitsubishi Tanabe, Asahi Kasei Pharma, AbbVie, Daiichi Sankyo, Bristol-Myers Squibb, Nipponkayaku, Janssen, Merck Serono, Takeda, Astellas, and Pfizer, Speakers bureau: AbbVie, Bristol-Myers Squibb, Chugai, Eisai, Janssen, Mitsubishi Tanabe, Pfizer, Takeda, Astellas, Daiichi Sankyo, Celtrion, and Nipponkayaku, Y. Tanaka Grant/research support from: BMS, MSD, Chugai, Mitsubishi Tanabe, Astellas, AbbVie, and Daiichi Sankyo, Speakers bureau: UCB Pharma, Mitsubishi Tanabe, Abbott, AbbVie, Eisai, Chugai, Janssen, Pfizer, Takeda, Astellas, Daiichi Sankyo, GSK, AstraZeneca, Eli Lilly, Quintiles, MSD, and Asahi Kasei Pharma, S. Soen Grant/research support from: Eisai, Daiichi Sankyo, and Takeda, Speakers bureau: Asahi Kasei Pharma, Astellas, Eisai, MSD, Ono Pharmaceutical, Daiichi Sankyo, Takeda, Chugai, Teijin Pharma, and Pfizer, H. Yamanaka Grant/research support from: UCB Pharma, AbbVie, Astellas, Bristol-Myers Squibb, Chugai, Eisai, Janssen, Mitsubishi Tanabe, Pfizer, and Takeda, Consultant for: UCB Pharma, AbbVie, Astellas, Bristol-Myers Squibb, Chugai, Eisai, Janssen, Mitsubishi Tanabe, Pfizer, and Takeda, T. Yoneda Consultant for: Daiichi Sankyo, S. Tanaka Consultant for: Amgen inc, Amgen Astellas, KYOCERA Medical, Daiichi Sankyo, Teijin Pharma, Asahi Kasei Pharma, Ono Pharmaceutical, Eli Lilly, and Pfizer, T. Nitta Employee of: Daiichi Sankyo, N. Okubo Shareholder of: Daiichi Sankyo, Employee of: Daiichi Sankyo, H. K. Genant Consultant for: Daiichi Sankyo, Pfizer, Amgen, BioClinica, Eli-Lilly, Janssen, Servier, Novartis, Takeda, Merck, Biomarin, Clemencia, Agnovos, and Regeneron, D. van der Heijde Consultant for: AbbVie, Amgen, Astellas, AstraZeneca, BMS, Boehringer Ingelheim, Celgene, Daiichi Sankyo, Eli-Lilly, Galapagos, Gilead, Janssen, Merck, Novartis, Pfizer, Regeneron, Roche, Sanofi, and UCB Pharma, Employee of: Imaging Rheumatology bv